Micro-Reflector Integrated Multichannel μLED Optogenetic Neurostimulator With Enhanced Intensity - Khan, Wasif; Setien, Monica; Purcell, Erin; Li, Wen (Frontiers in Mechanical Engineering, 2018)
This paper reports the fabrication and characterization of an optical neuro-stimulator array that consists of 32-channel microscale light-emitting diodes (μ-LEDs) coupled with microscale reflectors for intensity enhancement. The hemi-spherical micro-reflector is able to collect the rear side emission of LED while also acting as a collimator to focus the diverged LED light, aiming toward driving power minimization through light intensity increase, for wireless neuro-stimulator applications. The micro-reflector was constructed by wet etching of silicon followed by aluminum coating as the reflective mirror. The reflective cavity was filled with polydimethylsiloxane (PDMS) that acts as the planarization polymer to facilitate device integration with the μ-LED chip. Deviation of hemi-spherical geometry cavities due to the uneven lateral and vertical etching rate was shown, and the surface morphology was characterized experimentally. Optical intensity enhancement was studied in both simulation and experiments, demonstrating that the micro-reflector enables 65% intensity enhancement. The reflector-coupled LED had an operating temperature increase of <1°C, well within the ANSI/AAMI safety limit for biomedical implants. The potential of the stimulator for use in optogenetics was validated by in vitro experiments.